Implementasi Prinsip “Kepentingan Terbaik bagi Anak” dalam proses persidangan Anak secara elektronik pada masa pandemi di Kota Jakarta Barat - Yudha Pradana (Jurnal Ilmiah Hukum dan Hak Asasi Manusia, 2022)
Purpose: This study aims to analyze the implementation of one of the principles of child protection namely "Best interests of the child" in the virtual trial process. Research Methodology: The research method used in this research is the juridical-empirical method. The data used in this study include primary data and secondary data which are studied and analyzed systematically. The primary data in this study are observations and interviews with children in conflict with the law and other related parties, such as Judges and Probation Officers, while secondary data included laws and regulations and related literature. Result: The results shows that the implementation of the principle of the “best interests of the child: in the virtual trial process for children during the pandemic is yet not optimal due to insufficient fulfillment of children's rights during the virtual trial process. Limitation: The limitation of this research is that it only takes place in West Jakarta Jurisdiction. Contribution: This research is expected to provide benefits for law enforcement agencies to help them reach the best decision for children in conflict with the law and contributes to the development of legal studies, specifically in the criminal justice process of children.